Respostas

  • Usuário do Brainly
2013-06-28T00:43:22-03:00

Temos que:

 

\text{f}(\text{x})=\text{ax}+\text{b}

 

\text{f}(3)=1

 

\text{f}(-2)=4

 

Desta maneira, temos, 3\text{a}+\text{b}=1 e -2\text{a}+\text{b}=4.

 

Subtraindo essas equações, obtemos:

 

(3\text{a}+\text{b})-(-2\text{a}+\text{b})=1-4

 

5\text{a}=-3

 

\text{a}=\dfrac{-3}{5}

 

Desse modo, segue:

 

3\cdot\dfrac{-3}{5}+\text{b}=1

 

\dfrac{-9}{5}+\text{b}=1

 

\text{b}=1+\dfrac{9}{5}=\dfrac{14}{5}

 

Logo, \text{f}(\text{x})=\dfrac{-3\text{x}}{5}+\dfrac{14}{5}

1 5 1